1997
DOI: 10.1128/cdli.4.1.49-56.1997
|View full text |Cite
|
Sign up to set email alerts
|

Human humoral responses to antigens of Mycobacterium tuberculosis: immunodominance of high-molecular-mass antigens

Abstract: The selection of antigens of Mycobacterium tuberculosis for most studies of humoral responses in tuberculosis patients has been restricted to molecules that were either immunodominant in immunized animals or amenable to biochemical purification rather than those that were reactive with the human immune system. Delineation of antigens that elicit humoral responses during the natural course of disease progression in humans has been hindered by the presence of cross-reactive antibodies to conserved regions on ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Knowledge of serological markers for TB patients coinfected with HIV would facilitate the development of diagnostic tests for TB. A study designed to characterize the target of the antibody response revealed that an 88-kDa antigen from CFP reacted with 70% of sera from TB patients (23). This same 88-kDa antigen was able to detect antibody in 74% of sera from HIV-positive patients who later developed TB (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of serological markers for TB patients coinfected with HIV would facilitate the development of diagnostic tests for TB. A study designed to characterize the target of the antibody response revealed that an 88-kDa antigen from CFP reacted with 70% of sera from TB patients (23). This same 88-kDa antigen was able to detect antibody in 74% of sera from HIV-positive patients who later developed TB (22).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the reactivity of high-molecular-weight antigens with patient sera has been described. In particular, an 88-kDa antigen was found to elicit a strong antibody response in patients with TB (23). Most importantly, the 88-kDa antigen, which is present in M. tuberculosis culture filtrate proteins (CFP), also has been described as a surrogate marker for TB in HIV-seropositive individuals, but its peptide sequence has been elusive (22).…”
mentioning
confidence: 99%
“…Attempts to define the immunologically active components within this fraction have led to the purification and characterization of several proteins including the 6-kDa ESAT6 (56), 24-kDa MPT64 (39,47), 30-to 31-kDa Ag85 complex (21,24,39), and 45-kDa MPT32 (15,39,48). A strong humoral response against CFPs has also been noted (29), and antigens such as the 45-kDa MPT32 (18), the 38-kDa PstS homolog (9), and an 88-kDa protein complex (29,49) hold promise as tools for serodiagnosis.…”
mentioning
confidence: 99%
“…7 In several studies, positive antibody responses in patients with tuberculosis were found 60-90% with specificities of 91-100%. 8,9,10,11 The higher rate of seropositivity for the microscopy/culture positive TB patients compared to that for the microscopy/culture negative TB patients may be due to more bacillary load exposed to immune system leading to more antibody production. The cause of negative response among microscopy/culture positive patients of both pulmonary and extrapulmonary TB might be due to intracellular nature of the bacilli resulting in less or no exposure to the immune system, or it may be due to immunosuppressive condition of the patients.…”
Section: Western Blot Analysismentioning
confidence: 99%